2015
DOI: 10.1186/s13104-015-1435-y
|View full text |Cite
|
Sign up to set email alerts
|

Medication prescribing errors in the medical intensive care unit of Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia

Abstract: BackgroundMedication errors (MEs) are important problems in all hospitalized populations, especially in intensive care unit (ICU). Little is known about the prevalence of medication prescribing errors in the ICU of hospitals in Ethiopia. The aim of this study was to assess medication prescribing errors in the ICU of Tikur Anbessa Specialized Hospital using retrospective cross-sectional analysis of patient cards and medication charts.ResultsAbout 220 patient charts were reviewed with a total of 1311 patient-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 11 publications
(18 reference statements)
3
36
2
1
Order By: Relevance
“…Other countries had much higher MPE incidence rate. For example, Brazilian intensive care unit had 43.5 % MPEs, and Ethiopian, Saudi and Indian hospitals had 40 %, 56% and 34 % MPEs respectively [20,22,24,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other countries had much higher MPE incidence rate. For example, Brazilian intensive care unit had 43.5 % MPEs, and Ethiopian, Saudi and Indian hospitals had 40 %, 56% and 34 % MPEs respectively [20,22,24,29].…”
Section: Discussionmentioning
confidence: 99%
“…There was only one Iraqi study measuring medication errors by 2014 and this was an observational study (without interventions) which evaluated the types and medication classes of these errors [18]. Although several studies have investigated pharmacist interventions in prescribing errors around the world [6,8,[19][20][21][22][23][24][25], almost all of these studies were limited to evaluations of the incidence rate, causes, clinical significance and types of prescribing errors. However, a little is known about physician acceptance rate of pharmacist recommendations and only a couple of studies have focused on implementation of recommendations [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…6 Also in a retrospective cross-sectional study that was conducted at Tikur Anbessa Hospital in Ethiopia, the results were that 42.89% of the studied prescriptions were found to contain omission errors. 9 This shows that prescription writing errors are more to be encountered in various regions involving prescribing practice.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 But also considering that prescription order in our areas being hand written, there is a high susceptibility of committing errors in the process of prescription writing, but also due to the absence of any supporting system to aid prescribers, who rely mostly on their memory in order to avoid prescribing errors. 9 Few epidemiological statistics have been put forward with regard to common prescription writing errors in the developing countries. 9 In Tanzania, studies have shown also that prescription writing errors are commonly encountered8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation